Silêncio constitucional como objeto da interpretação: conceito, categorias e função operativa no sistema jurídico - Gil, Arilson Garcia (2022)
The object of the present work is constitutional silence. In the course of the research it was verified that the delimitation of the constitutional silence as an object of interpretation is a precondition of the juridical rationality of judicial decisions for the enforcement of fundamental rights and directly affects the implementation of social justice and the recognition of a plural society. Therefore, the constitutional silence, depending on its interpretation, can be an obstacle or a way to develop the objectives of the Democratic Rule of Law, due to the lack of methodological uniformity and hermeneutic categories in the interpretation of the constitutional silence and the juridical insecurity caused by the insufficient control of the rationality of judicial decisions. For the constitutional silence to constitute one of the ways of development of the Democratic Rule of Law, this work proposes to study it, especially to systematize the theme with the delimitation of concepts, categories and operative function, according to the paradigm established from the Federal Constitution of 1988. The theories of the Constitution as an open order, the multi-level legal system, constitutional mutations, judicial activism, language, social systems and the systemic-constructionist view of Law were used as main references. The central conclusions of the work are the concept of constitutional silence as a potentiality for the evolution of the Constitution, and proposals for categories and the operative function of silence to update and adequate the theories adopted by the doctrine and by the Brazilian Supreme Court